2016
DOI: 10.1002/aoc.3645
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and X‐ray structural characterization of new polymeric organotin(IV) carboxylates and their in vitro antifungal activities: Part II

Abstract: Funding informationCNPq, CAPES and FAPEMIG The reactions of R 3 SnCl (R = Me, Bu or Ph) with sodium 4-phenylbutyrate, Na(OPh b ), in EtOH yielded three polymeric triorganotin carboxylates, namely [R 3 Sn(OPh b )] n (R = Me (1), Bu (2) or Ph (3)). All complexes were spectroscopically characterized using Fourier transform infrared, 119 Sn Mössbauer, 1 H NMR, 13 C{ 1 H} NMR and 119 Sn{ 1 H} NMR spectral techniques. In addition, the crystal structures of 1 and 3 were determined using single-crystal X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…For complexes 1a-1d the Δν calculated values are ranging from 286 to 326 cm −1 . A Δν (COO) > 200 cm −1 is attributable to the formation of a covalent metal oxygen bond and a monodentate coordination mode of the carboxylic group bonded to the tin atom (see Table S1) [52,53]. The coordination of both lone pair of the nitrogen atoms from pyridine and azomethine to the tin was confirmed by the existence of a vibration band at 415 cm −1 , corresponding to Sn-N.…”
Section: Synthesis and Characterization Of Heptacoordinated Organotin (Iv) Complexes Complexes 1a-dmentioning
confidence: 96%
“…For complexes 1a-1d the Δν calculated values are ranging from 286 to 326 cm −1 . A Δν (COO) > 200 cm −1 is attributable to the formation of a covalent metal oxygen bond and a monodentate coordination mode of the carboxylic group bonded to the tin atom (see Table S1) [52,53]. The coordination of both lone pair of the nitrogen atoms from pyridine and azomethine to the tin was confirmed by the existence of a vibration band at 415 cm −1 , corresponding to Sn-N.…”
Section: Synthesis and Characterization Of Heptacoordinated Organotin (Iv) Complexes Complexes 1a-dmentioning
confidence: 96%
“…Vários relatos documentados na literatura registram possíveis aplicações de complexos organoestânicos como agentes antimicrobianos, antitumorais, antifúngicos, antimaláricos e anti-inflamatórios. [69][70][71][72][73][74][75][76][77][78] Em contrapartida outros artigos enfatizam alguns aspectos prejudiciais dos organoestânicos, tais como os efeitos citotóxicos, genotóxicos, mutagénicos e neurotóxico. 79 Apesar desses aspectos negativos, têm-se estudado os possíveis mecanismos de ação e os resultados de dose-resposta, bastante necessários caso se queira explorar os efeitos terapêuticos dessa classe de compostos e de seus complexos de coordenação.…”
Section: Organoestânicos Como Agentes Biocidasunclassified
“…The current results from the study on organotin(IV) compounds have revealed that some organotin(IV) carboxylates show promising activities in many biological tests. For example, they have been widely used in the biological activities as antifungal (3,(7)(8)(9), antioxidant activities (10,11), antimalarial and antiplasmodial agents (12)(13)(14)(15), antiviral agents (16,17), antitumor and anticancer (18)(19)(20), corrosion inhibitor (21)(22)(23) and antibacterial (24)(25)(26)(27)(28)(29)(30). Moreover, these compounds have been found to exhibit strong activity as disinfectant (31).…”
Section: Introductionmentioning
confidence: 99%